Determining the Structural Design of a Plow to Reduce Energy Costs of Basic Soil Tillage - F. N. Grakov; A. V. Gritsenko; V. A. Alyab'ev (Сельскохозяйственные машины и технологии, 2019)
Sharp fluctuation in the traction resistance of a moldboard plow arising when changing working conditions can be decreased by improving the plow design. (Research purpose) To reduce or eliminate changes in the traction resistance of a plow using automatic tillage depth regulators, which will reduce the energy consumption of the unit and, therefore, increase its productivity. (Materials and methods) The authors considered two different groups of moldboard plows differing in the type of the frame fastening to the tractor suspension axis, and examined their advantages and disadvantages. To determine the rational design parameters of a plow, they estimated the influence of the relative position of working bodies on the traction resistance and tillage depth, as well as on the change in the shape and transverse area of a soil layer. (Results and discussion) The paper presents the established relationships, which show that when the angle of a working body is set in the transverse plane upward, there is a jump in traction resistance depending on the overlap amount of the working bodies. The study has revealed the relationship between traction resistance and the position of the plow rotation axis: the less the plow deviates from its rotation axis, the more intensively traction resistance decreases. Three structural designs of plows used on the soil with a resistivity of 0.8 kilograms per square centimeter have been analyzed and the most appropriate design has been chosen. It was determined that the change in traction resistance per unit of change in the average depth of plowing for the first plow scheme 146 kilograms per centimeter, for the second – 128, for the third – 210 kilograms per centimeter. (Conclusions) It has been revealed that the best structural design is that of a semi-mounted plow having a hinge-joint connection with a tractor in the transverse plane and support wheels resting on the field surface. Plows with this structural design have shown high technological reliability in tests, as well as a significant increase in productivity (with draft control of up to 10-11 percent) without deteriorating the working conditions of a tractor driver and field performance indicators.